2006
DOI: 10.1080/02671520600793757
|View full text |Cite
|
Sign up to set email alerts
|

Can different teaching strategies or methods of preparing pupils lead to greater improvements from GCSE to A level performance?

Abstract: There is no published empirically based research on the new GCE synoptic assessment. Consequently no published research has been undertaken on its role, how it is taught or how pupils are prepared for the assessment. Neither is there a published evaluation of the effectiveness of teaching the synoptic units. It is these issues which are addressed in the present study. One hundred and twenty-five chemistry teachers replied to a questionnaire about the teaching strategies that they used and how they prepared can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Ultimately, then, for students the notion of 'predictability' as it plays out in the public dialogues was not one that they seemed to 'own'; they could see why perhaps policy-makers, politicians, media commentators might define it in the negative way that they do, but such definitions were not of immediate importance to them; in their every day experiences a degree of predictability was a positive aspect of examinations and one that is not, in all cases for all students, necessarily problematical. Whilst many of the studies on the impact of high-stakes tests suggest that some teachers narrow the curriculum for their students (Madaus, Russell and Higgins 2009;Greatorex and Malacova, 2006), this study shows that students narrow the curriculum for themselves. They are agentive in adjusting their learning behaviours and practices accordingly in order to both cope with the demands of highstakes examinations but also to do well.…”
Section: Discussionmentioning
confidence: 96%
“…Ultimately, then, for students the notion of 'predictability' as it plays out in the public dialogues was not one that they seemed to 'own'; they could see why perhaps policy-makers, politicians, media commentators might define it in the negative way that they do, but such definitions were not of immediate importance to them; in their every day experiences a degree of predictability was a positive aspect of examinations and one that is not, in all cases for all students, necessarily problematical. Whilst many of the studies on the impact of high-stakes tests suggest that some teachers narrow the curriculum for their students (Madaus, Russell and Higgins 2009;Greatorex and Malacova, 2006), this study shows that students narrow the curriculum for themselves. They are agentive in adjusting their learning behaviours and practices accordingly in order to both cope with the demands of highstakes examinations but also to do well.…”
Section: Discussionmentioning
confidence: 96%
“…Jones et al support that teaching on problem solving is shaped by, and for, the examination. Indeed, Greatorex and Malacova (2006) found that any coursework or examination is closely related to the teaching strategies. This said, research on interactive teaching practices and summative assessment should be synchronized in a realistic perspective to impact positively on educational systems.…”
Section: Further Discussionmentioning
confidence: 99%